SYNTHESIS, CHARACTERIZATION AND APPLICATION OF DIATOMACEOUS EARTH – 4,4-DIAMINODIPHENYLETHER-O-HYDROXYBENZALDEHYDE AS AN ADSORBENT OF Ag(I) METAL ION - Ahmad Fatoni; Soerja Koesnarpadi; Nurlisa Hidayati (Universitas Gadjah Mada, 2010)
Synthesis, characterization and application of Diatomaceous Earth-4,4-Diamino diphenylether-O-Hydroxybenzaldehyde (diatomaceous earth-DDE-O-Hb) as an adsorbent of Ag(I) metal ion has been done. The aim of the purification of natural diatomaceous earth with KMnO4, H2SO4 and HCl were to obtain pure diatomaceous earth, remove the other compounds and de-alumination, respectively. The adsorbent of diatomaceous earth-DDE-O-Hb was synthesized by reacting pure diatomaceous earth with 3-chloropropyltrimethoxysilane, 4,4-diaminodiphenylether (DDE) and O-hydroxybenzaldehyde (O-Hb). The FTIR spectroscopy was used to identify Schiff base group in diatomaceous earth-DDE-O-Hb adsorbent. The diatomaceous earth-DDE-O-Hb was applied as adsorbent in the adsorption of Ag(I) metal ion. Parameters influencing the interaction such as time, pH and concentration were optimized. The result showed that diatomaceous earth-DDE-O-Hb adsorbent have Schiff base group. The interaction time of 90 min showed that 70.79% of Ag(I) metal ions at the concentration of 100 ppm can be adsorbed by diatomaceous earth-DDE-O-Hb adsorbent. At the pH solution between 2 to 7, the concentration of 100 ppm of Ag(I) metal ion that can adsorbed by diatomaceous earth-DDE-O-Hb adsorbent was up to 98% and at the concentration of 25 ppm Ag(I) metal ion, the adsorption of Ag(I) by diatomaceous earth-DDE-O-Hb adsorbent was near 91%.